2019
DOI: 10.1038/s41598-018-36400-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphologic study of retinal hypoperfusion injury induced by bilateral common carotid artery occlusion in rats

Abstract: Retinal hypoperfusion injury is the pathophysiologic basis of ocular ischemic syndrome (OIS) which often leads to severe visual loss. In this study, we aimed to establish a rat model of retinal chronic hypoperfusion by bilateral common carotid artery occlusion (BCCAO) and observe changes in the retinal function and morphology. We found that model rats showed retinal arteriosclerosis, slight dilated retinal vein, small hemangiomas, hemorrhages, vascular segmental filling, and nonperfused areas after 2 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Full-size DOI: 10.7717/peerj.11665/fig- 5 et Qin et al, 2019;Sun et al, 2019;Yamamoto et al, 2006), milder retinal ischemic stress is observed in this UCCAO model. In this regard, retinal thinning was not dramatically observed in a short-term period even though there was retinal cell death.…”
Section: ; Lavinskymentioning
confidence: 72%
See 1 more Smart Citation
“…Full-size DOI: 10.7717/peerj.11665/fig- 5 et Qin et al, 2019;Sun et al, 2019;Yamamoto et al, 2006), milder retinal ischemic stress is observed in this UCCAO model. In this regard, retinal thinning was not dramatically observed in a short-term period even though there was retinal cell death.…”
Section: ; Lavinskymentioning
confidence: 72%
“…It is associated with a huge range of clinical ocular disorders and diseases such as diabetic retinopathy, glaucoma, optic neuropathies and stroke ( Dattilo, Newman & Biousse, 2018 ; Fouda et al, 2020 ; Minhas, Morishita & Anand, 2012 ; Osborne et al, 2004 ). As oxygen (directly referred to as “blood”) in the retina is supplied through the ophthalmic artery originated from the internal carotid artery, one of two branches of the common carotid artery (CCA), animal models by common carotid artery occlusion or stenosis (CCAO or CCAS) have been used to understand the pathogenesis of retinal ischemia ( Crespo-Garcia et al, 2018 ; Davidson et al, 2000 ; Lavinsky et al, 2006 ; Lee et al, 2020b ; Qin et al, 2019 ; Sun et al., 2019 ; Venkat, Chopp & Chen, 2015 ; Wellons Iii et al., 2000 ; Yamamoto et al, 2006 ; Yang et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Murine experimental models of carotid artery occlusion have been used to unravel pathological mechanisms for ocular ischemia [ 9 , 10 , 11 , 12 , 13 , 14 ]. Anatomically, the central retinal artery is derived from the ophthalmic artery, one of the branches of the internal carotid artery of the common carotid artery.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, carotid artery occlusion could potentially induce CRAO, finally leading to ocular ischemia and vision loss [ 15 , 16 ]. Bilateral common carotid artery occlusion to induce ocular ischemia has been applied to rats, in that the circle of Willis in rats is well-organized [ 9 , 10 , 11 , 12 , 13 , 17 ]. However, several studies reported that bilateral common carotid artery occlusion could not be applicable to mice with a high rate of death (almost 100%) because of a lack of posterior communicating arteries in the circle of Willis in mice [ 14 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…BCCAO also induces chronic ocular ischemia as the blood supply of the highly vascularized rodent retina comes from the internal carotid artery 20 . The retrograde neurodegeneration of the visual system results in the dysfunction of cortical neurons 21,22 . It could cause extensive structural remodeling in the visual cortex affecting the hypoperfusion-induced changes of the cortical proteome.…”
mentioning
confidence: 99%